Coating of Titanium Nitride Thin Film on Stainless Steel Using an RF Planar Coil Inductively Coupled Plasma - S.P, Chew; C.S, Wong (Malaysian Journal of Science, 2002)
Titanium nitride (TiN) thin film is grown on 304-stainless steel plate by Plasma Enhanced Physical Vapour Deposition (PEPVD) method in an RF Planar Coil Inductively Coupled Plasma (PC ICP) system. H-mode discharge in $Ar-N_{2}$ admixture is produced for this purpose. The titanium target is biased at a negative voltage of Ã¢â‚¬â€800V, while the substrate is biased at voltage ranging from 0 to Ã¢â‚¬â€160V in step of 20V to study the effect of substrate bias voltage on the quality of the TiN thin film obtained. The composition and structure of the films are studied and investigated by XRD, EPMA, AFM and SEM. The results show that bad quality TiN thin film is obtained when the substrate bias voltage is lower than Ã¢â‚¬â€60 V. With a substrate bias voltage of greater than Ã¢â‚¬â€80 V, a nominal TiN deposition rate of better than 1 $μ m$ per hour can be achieved.